2012
DOI: 10.1037/a0025042
|View full text |Cite
|
Sign up to set email alerts
|

A novel clinical test of recognition reaction time in healthy adults.

Abstract: We evaluated a clinical “go/no-go” reaction time test (recognition RTclin) that is portable and does not require a computer, and used it to quantify the effect of age on recognition RTclin test scores. Fifty-two healthy adults aged 19 – 83 years completed simple and recognition RTclin testing. Simple RTclin was measured as the elapsed time from initial release of a suspended vertical shaft by the examiner until its arrest by participant pinch grip. Recognition RTclin was similar except that a light on the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
2
35
0
2
Order By: Relevance
“…These findings support at least three novel, clinically relevant concepts: 1) When the data reported here are considered with prior work 27 RT clin appears to be an innovative, clinically accessible method for measuring inhibitory executive function over a brief time interval; 2) The data link RT clin based Short Latency Neurocognitive Attributes to UST and frontal plane responses to sequential perturbations during walking, and in so doing provide a mechanism by which poor inhibitory executive function increases fall risk; and 3) The relationships between Complex RT clin Accuracy:Simple RT clin Latency and measures of balance, frontal plane gait control, and major injuries were identified predominantly in the subjects with DPN suggesting that short latency neurocognitive capability is of greater importance in the setting of lower limb neuromuscular impairment. These points are addressed in sequence below.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings support at least three novel, clinically relevant concepts: 1) When the data reported here are considered with prior work 27 RT clin appears to be an innovative, clinically accessible method for measuring inhibitory executive function over a brief time interval; 2) The data link RT clin based Short Latency Neurocognitive Attributes to UST and frontal plane responses to sequential perturbations during walking, and in so doing provide a mechanism by which poor inhibitory executive function increases fall risk; and 3) The relationships between Complex RT clin Accuracy:Simple RT clin Latency and measures of balance, frontal plane gait control, and major injuries were identified predominantly in the subjects with DPN suggesting that short latency neurocognitive capability is of greater importance in the setting of lower limb neuromuscular impairment. These points are addressed in sequence below.…”
Section: Discussionsupporting
confidence: 79%
“…26 Complex RT clin Accuracy requires the subject to catch the same device solely on the randomly-determined 50% of trials in which lights affixed to it illuminate. 27 Simple RT clin Latency is measured in ms, and Complex RT clin Accuracy is measured as the percentage of trials in which the subject responds correctly. Simple RT clin Latency requires sustained attention and rapid reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is noted that this time frame is an arbitrary one, the expert panel agreed nevertheless that a period of rest was important prior to assessment. Future research should consider the efficacy for inclusion of vision tests such as the King Devick Test and clinical reaction time tests 155 156. Recent studies suggest that these may be useful additions to the sideline assessment of concussion.…”
Section: Section 3: Zurich 2012 Consensus Questionsmentioning
confidence: 99%
“…Future concussion consensus group research recommendations have suggested the looking at efficacy for inclusion of vision tests such as King-Devick and clinical reaction time tests, which will have limitations for many athletes with disability including those with visual impairment 8,40,41 or neuromuscular impairment, such as cerebral palsy. Furthermore, learning disability often goes unrecognized in sporting environments.…”
Section: Au10mentioning
confidence: 99%